Circular RNAs in pulmonary hypertension: Emerging biological concepts and potential mechanism. Issue 1 (27th January 2022) - Wang, Qian; Sun, Yuanyuan; Zhao, Qinhua; Wu, Wenhui; Wang, Lan; Miao, Yuqing; Yuan, Ping
Abstract: Circular RNAs (circRNAs) are endogenous RNAs with a covalently closed single‐stranded transcript. They are a novel class of genomic regulators that are linked to many important development and disease processes and are being pursued as clinical and therapeutic targets. Using the most powerful RNA sequencing and bioinformatics techniques, a large number of circRNAs have been identified and further functional studies have been performed. It is known that circRNAs act as potential biomarkers, sponges for microRNAs (miRNAs) and RNA‐binding proteins (RBPs), and regulators of mRNA transcription. They also participate in the translation of peptides or proteins. Many types of circRNAs are dysregulated in plasma or lung tissues, and they may be involved in regulating the proliferation and apoptosis of pulmonary artery endothelial cells (PAECs) and pulmonary artery smooth muscle cells (PASMCs), leading to pulmonary vascular remodeling in pulmonary hypertension (PH). One possible mechanism is that circRNAs can regulate the function of PAECs and PASMCs by acting as miRNA sponge. However, other potential mechanisms of action of circRNAs are still being actively explored in PH. This paper presents a systematic review of the biogenesis, biological characterization, relevant underlying functions, and future perspectives for studies of circRNAs in the pathogenesis of PH. Abstract : Circular RNAs (circRNAs) are a novel class of genomic regulators that are linked to the process of pulmonary hypertension (PH) and are being pursued as clinical and therapeutic targets. The limited PH‐related circRNAs studies mainly focus on the functions as miRNA sponges and the current research clearly indicated that circRNAs had a critical effect on the pathogenesis of PH. They might involve in regulating the proliferation, migration and apoptosis of pulmonary artery smooth muscle cells (PASMCs), leading to pulmonary vascular remodeling in PH.